Influencing factors and environmental effects of interactions between goethite and organic matter: A critical review - Yi, Shuqi; Chen, Xiaorui; Cao, Xu; Yi, Bing; He, Wei (Frontiers in Environmental Science, 2022)
This paper reviews the research progress on the interactions between goethite and organic matter and its environmental effects in recent decades. The interactions mainly include the effect of organic matter on the surface properties and the crystallization of goethite and the adsorption/binding between organic matter and goethite, which can be depicted by the commonly used surface complexation models include charge distribution multi-site complexation model (CD-MUSIC model), ligand charge distribution model (LCD model), and natural organic matter charge distribution model (NOM-CD model). The influencing factors of the interaction are summarized with emphasis on the external, including pH, ionic strength, carbon dioxide (CO2), and the internal, including the structure of organic matter and iron species. The goethite – organic matter complexes caused by the interactions will affect migration and transformation of conventional heavy metals and emerging antibiotics. The complexes, as the carrier of carbon and iron, are also the critical parts of the carbon and iron cycles, which are associated with climate change. This review provides a basis for future mechanism studies of formation, transformation, effects of goethite – organic matter complexes (particulate organic matter or carbon-contained minerals) in different environmental systems at a molecular level.